Influence of the inner tilt angle on downwash airflow field of multi-rotor UAV based on wireless wind speed acquisition system - Wang, Ling; Hou, Qihang; Wang, Junpeng; Wang, Zhiwei; Wang, Shumao (International Journal of Agricultural and Biological Engineering, 2021)
The downwash airflow field is an important factor influencing the spraying performance of plant protection UAV, and the structural design of rotors directly affects the characteristics of the downwash airflow field. Therefore, in this study, three-dimensional models of a six-rotor UAV with various inner tilt angles were established to simulate and analyze the influence of the inner tilt angle on the downwash airflow field based on the Reynolds average NS equation, RNG k-ε turbulence model, etc.. On this basis, a wireless wind speed acquisition system using the TCP server was developed to carry out the test through the marked points with real-time detection. The simulation results show that, the variation of inner tilt angles of the six-rotor UAV did not cause significant difference in the time dimension of the downwash airflow field, and with the change of the inner tilt angle from 0° to 8°, the distribution of downwash airflow field tended to obliquely shrink towards the central axis direction, and the amplitude of linear attenuation of airflow speed was also increased, which the difference of attenuation amplitude was 1 m/s. Besides, under the different inner tilt angle, the airflow velocity in “lead in area” was significantly greater than that in the “lead out area”, and the difference of air velocity distribution in space would affect the uniformity of droplet deposition. Through the calibration test, the measurement accuracy error of the developed system was lower than 0.3 m/s, and the adjusted R2 of the calibration fitting equation was higher than 0.99. The test and simulation values at test points from 0.2-2.3 m below the rotors exhibit the same variation trend, and the average relative error at the height of 1.1-2.3 m below the rotors and 0.2-0.8 m near the ground was within 10% and 20%, respectively. The simulation and test results were highly reliable, which could provide basis and reference for the design and optimization of plant protection drones. Keywords: plant protection UAV, downwash airflow field, inner tilt angle, numerical simulation, wind speed acquisition DOI: 10.25165/j.ijabe.20211406.6477 Citation: Wang L, Hou Q, Wang J P, Wang Z W, Wang S M. Influence of inner tilt angle on downwash airflow field of multi-rotor UAV based on wireless wind speed acquisition system. Int J Agric & Biol Eng, 2021; 14(6): 19–26.